Transarterial chemoembolization (TACE) in hepatocellular carcinoma BCLC B patients: case series - Ni Nyoman Widyasari; Firman Parulian Sitanggang; Putu Patriawan; Dewa Gede Mahiswara (Intisari Sains Medis, 2021)
Introduction: Hepatocellular carcinoma (HCC) is the fifth leading cause of death for men and the seventh for women worldwide, HCC is one out of 10 most cancers in Indonesia. HCC grows in the background of chronic liver disease and often associated with hepatitis virus infection such as hepatitis B virus (HBV) and hepatitis C virus (HCV).  Transarterial chemoembolization (TACE) is a minimally invasive procedure performed by interventional radiologist as the treatment of choice for intermediate stage HCC.Case report: Here in we report a 62 and 59 years old female with hepatocellular carcinoma Barcelona clinic liver cancer (BCLC) B who were treated with TACE using 50 mg doxorubicin mixed with Iopamiro and lipiodol. Both were patients with history of HBV infection. After 5 weeks of TACE, triphase abdominal CT-Scan was done to evaluate tumour progression, however one patient was loss to follow up.  Evaluation of one patient was done and revealed more than 30% decrease  solid viable tumour with increase of necrotic area.  Expansion of necrotic area is one of the HCC treatment response criteria, while decrease tumour enhancement explains the viability of the tumour itself.Conclusion: TACE is the therapy of choice for patient with HCC BCLC B, which can give enlargement of necrotic area and decrease tumour viability.